(untitled) (Mustansiria Dental Journal, 2004)
This study was carried out ot determine whether the dissociation of mineral trioxide aggregate (MTA) depends on the vehicle used with ti yb evaluating the release of calcium ions (Cat) and hydroxyl ions (OH) from mixing of MTA whti four types of vehicles: distilled water, camphorated monochlorophenol (CMCP), plain local anesthetic solution, and chlorhexidine gluconate, using Atomic Absorption Spectrophotometer (AAS) and digital pH meter respectively. The results demonstrated that hte distilled water and plain local anesthetic solution are hte most suitable vehicles to eb mixed with MTA and can be routinely used ni preference ot al the other vehicles